Resilience and life-cycle performance of smart bridges with shape memory alloy (SMA)-cable-based bearings. (15th January 2018) - Zheng, Yue; Dong, You; Li, Yaohan
Highlights: An approach to evaluate life-cycle loss and resilience of novel bridges is proposed. Fragility curves of bridges with SMA-cable-based bearings are assessed. Development of smart bridges using SMA is proposed. Life-cycle loss and resilience are assessed considering representative hazards. A decision-making tool for application of smart materials is provided. Abstract: Due to its unique properties within hazard mitigation, shape memory alloy (SMA) has been developed and adopted within the design and retrofit of civil infrastructures to improve the seismic performance. The performance benefit associated with the SMA bridges in a long term has not been well recognized by the decision maker, thus, the wide application of SMA within the civil infrastructures is still limited. This paper aims to apply the resilience and life-cycle loss assessment to the comparative performance assessment of novel and conventional bridges and to promote the application of smart materials within the civil engineering. Both the direct and indirect costs are considered within the life-cycle assessment process. Specifically, the corresponding structural performance, resilience, and life-cycle loss associated with different bridge systems are addressed. The methodology accounts for the life-cycle loss assessment considering the representative hazard scenarios that could happen within the investigated region. The proposed approach is applied to highway bridges with and without using the SMA-cable-based bearings. The benefit associated with the application of the proposed novel bearing is quantified in terms of resilience and life-cycle loss.